Adesão ao tratamento por pacientes portadores de diabetes tipo 1 e tipo 2: efeitos do treino de discriminação de dicas internas e externas - BRANDÃO, Washington Luiz de Oliveira (2003)
The present study aims to compare the results of discriminatioll training of symptoms and actions related to the treatment of Type I and Type 2 diabetes, evaluating the effectíveness of these trainings for the estimation of glicemic levels and adherence to the treatment. A countless number of surveys carried on in the Health psychology field has the goal of improving the treatment to diabetic patients. Part of these surveys use a procedure caUed general blood glucose selfmonitoring which is based on skills such as observation, checking and registering the relevant aspects in the treatment of diabetes such as: (a) glícemic leveI (GL); (b) symptoms (internal cues - 1C); and (c) actions related to the treatment such as medication, nourishment and physical activity (external cues - EC). The studieshave shownthat general blood glucose.self-monitoring helps the patients to improve the levei of discrimination ofthe glicemic a1terations. This 1iterature is not clear about defining which is the best cue to the used to improve the discrimination of the glicemic levels and states that the development of this skill does not enhance the adherence to the treatment. This study was made of three distinct phases: (a) Baseline and introdutory interview; (b) Trainings interviews; (c) Devolutive final interview. The training phase is divided ln two parts - Internal Cues (IC) and External Cues (EC). During the training phases the participants estimated and assigned a cause to the glicemic leveI on their blood stream measured by a memory-containing reflectometer in the interviews. During in the EC, the participantes also received a feedback from the researcher about the report of the directions followed, based on the directions given by medical advice and compiled from medical registers ofthe patients. 1ts rate of adherence (RA) was measured in the two first phases. The training interviews were conducted at 'the participant's home, in the intervals of 3 days, during which the participants registered the events which took place during corresponding phase. The results showed that independently of the type of training which was accomplished, the participants estimated their glicemic levels based on external cues. The symptoms related to 1Cphase were not always associated to glicemic leveI measured. The participants with diabetes Type 1 reached a higher degree of precision on their estimations during the EC training. The majority of participants had higher degree of the adherence to the treatment when they stared by the EC training. The results suggest that: (a) the reports of the symptoms are not the best indication to evaluate glicemic leveI and adherence of treatment; (b) the best type of training to enhance the adherence to the treatment is the one which involves external cues